Microalgae in two freshwater lakes and an estuary as a result of groundwater contamination from households. Issue 2 (4th May 2019) - Bate, G. C.; Matcher, G. F.; Venkatachalam, S.; Meiklejohn, I.; Dorrington, R. A.
Abstract : The increasing incidence of cyanobacterial blooms in Southern African aquatic systems is raising concern about the potential for these microorganisms to contaminate potable water with toxic secondary metabolites. This study focused on two lakes, an estuary and the sea in a small catchment in Maputaland, northern KwaZulu Natal, South Africa, fed by groundwater impacted by sewage effluent discharged from houses and residential complexes. The important effluents identified were nitrate, nitrite, ammonium-N and ortho-phosphate at concentrations above that which might be expected in a sandy catchment where all the water emanates from rainfall averaging about 1000 mm per annum. Analyses of the microalgae in two freshwater lakes showed that cyanophytes made up over 88% of the phytoplankton in the larger Lake Mgobezeleni and over 50% in the smaller Lake Shazibe. This raises concerns about the potential health risk to communities using this water for domestic, agricultural and recreational purposes. Microscope images showed the cyanophytes to be embedded in mucus. Next Generation Sequencing analysis of bacterial 16S rRNA genes showed a persistent cyanobacterial bloom in Lake Mgobezeleni, including cyanobacterial taxa closely related to species that are known to produce cyanotoxins, including Microcystis aeruginosa, which produces the hepatotoxin microcystin. Other less dominant potential cyanotoxin producers were detected in all the water bodies sampled. These results highlight the importance of identifying water systems at risk of experiencing cytotoxic cyanobacterial blooms and, most importantly, the need to monitor such vulnerable systems to ensure the safety of surrounding communities. Where the groundwater is being used by householders with boreholes, the nitrogen and phosphate concentrations were within South African drinking water quality standards but the presence of cyanophytes appears to indicate that the target environmental water quality standards published by the government are too high for this area.